Road traffic noise and cognitive function in older adults: a cross-sectional investigation of The Irish Longitudinal Study on Ageing - Ciarán Mac Domhnaill; Owen Douglas; Seán Lyons; Enda Murphy; Anne Nolan (BMC, 2021)
Abstract Background The World Health Organization published updated Environmental Noise Guidelines in 2018. Included are recommended limit values for environmental noise exposure based on systematic reviews for a range of health outcomes, including cognitive impairment. There is emerging evidence in the literature that chronic exposure to road traffic noise may affect cognitive function in older adults, but this relationship is not well established. This study spatially linked nationally representative health microdata from The Irish Longitudinal Study on Ageing to building-level modelled noise data for two cities in the Republic of Ireland. This was used to investigate associations between exposure to road traffic noise and cognitive function in a sample of older adults, independent of a range of socio-demographic and behavioural characteristics, as well as exposure to air pollution. Methods We used the Predictor-LimA Advanced V2019.02 software package to estimate noise originating from road traffic for the cities of Dublin and Cork in Ireland according to the new common noise assessment methodology for the European Union (CNOSSOS-EU). Noise exposure values were calculated for each building and spatially linked with geo-coded TILDA microdata for 1706 individuals aged 54 and over in the two cities. Ordinary least squares linear regression models were estimated for eight standardised cognitive tests including noise exposure as an independent variable, with standard errors clustered at the household level. Models were adjusted for individual sociodemographic, behavioural and environmental characteristics. Results We find some evidence that road traffic noise exposure is negatively associated with executive function, as measured by the Animal Naming Test, among our sample of older adults. This association appears to be accounted for by exposure to air pollution when focusing on a sub-sample. We do not find evidence of an association between noise exposure and memory or processing speed. Conclusions Long term exposure to road traffic noise may be negatively associated with executive function among older adults.